Participation in occupations, health and adjustment during the transition from military service: A cross-sectional study. Issue 5 (3rd September 2021) - Carra, Kylie; Curtin, Michael; Fortune, Tracy; Gordon, Brett
ABSTRACT: Participation in meaningful occupations is central to health, well-being, and adjustment during the transition from military service. The aim of the present study was to identify what occupations transitioning Australian Defence Force members participate in for the purpose of improving their health and well-being. A secondary aim was to identify if participation in various occupations was associated with better self-reported health and/or adjustment outcomes. One hundred and ninety-eight former Australian Defence Force members discharged on or after January 1, 2004 responded to a cross-sectional survey measuring adjustment, physical and mental health, and participation in occupations. Occupations were coded using the Time Use Classification system developed by the Australian Bureau of Statistics. An easier adjustment was reported by former service members who participated in employment-related activities, domestic activities, voluntary work and care activities, and social and community interaction ( MD = −0.63 to −0.45, d = .37 to .52). Participation in employment-related activities, social and community interaction, and sport and outdoor activity was associated with better physical health ( MD = 3.20 to 3.73, d = .34 to .40). Participation in employment-related activities was also associated with better mental health ( MD = −3.75, d = .54). This research indicates that participation in occupation is a factor that may be utilized with former service members to positively influence health and adjustment during military transitions. Given differences in participation and outcomes among different sub-groups, it is recommended that occupation-based programs be tailored to individual preferences and transition needs.